The Relationship Between Patients’ Perceptions of Nurses’ Therapeutic Communication with Service Satisfaction and Self-Care Levels Among Inpatients - Kusuma, Erik; Kurniawan, Dicky Endrian; Kurnianto, Syaifuddin; Widianto, Eko Prasetya; Wibowo, Suhendra Agung; Paraswati, Mareta Deka (Babali Nursing Research, 2026)
Introduction: Nurses’ therapeutic communication is a key element in enhancing patients’ experiences during hospitalization; however, its simultaneous impact on service satisfaction and self-care remains underexplored, particularly in regional hospitals in Indonesia. This study aims to analyze the relationship between patients’ perceptions of nurses’ therapeutic communication and their service satisfaction and self-care levels among inpatients.Methods: A cross-sectional analytical study was conducted on 110 patients at the inpatient ward of a type C hospital. Data were collected using the Nurse–Patient Communication Questionnaire (NPCQ; 15 items), a validated 7-item modified Patient Satisfaction Questionnaire (PSQ-18), and the Self-Care Ability Scale (SCAS; 12 items). Spearman’s correlation and simple linear regression analyses were performed, with statistical significance set at p < 0.05.Results: Patients reported high perceptions of therapeutic communication (mean = 48.2/60), high service satisfaction (mean = 28.6/35), and moderate to high self-care ability (mean = 36.8/48). Therapeutic communication demonstrated a strong positive correlation with service satisfaction (r = 0.68, p < 0.001) and a moderate-to-strong correlation with self-care (r = 0.59, p < 0.001). Regression analysis revealed that therapeutic communication explained 45% of the variance in satisfaction and 34% of the variance in self-care. Notably, while respect and information clarity scored highest (means = 3.6–3.8), patient involvement in care decisions was the lowest-rated dimension (mean = 2.7).Conclusion: Therapeutic communication serves as a dual-impact clinical competency that enhances both emotional satisfaction and functional self-care. These findings call on hospital administrators and nursing educators to institutionalize communication training as a core, measurable component of nursing practice, not as a soft skill, especially in resource-constrained settings.